Conductive member, process cartridge and electrophotographic image forming apparatus

The conductive member with a specific matrix-domain structure and volume resistivity profile addresses the challenge of suppressing abnormal discharge and ensuring sufficient charging, resulting in high-quality electrophotographic images.

JP7669134B2Active Publication Date: 2025-04-28CANON KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020171435
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-18
Filing Date
2020-10-09
Publication Date
2025-04-28
Estimated Expiration
2040-10-09

AI Technical Summary

Technical Problem

Existing conductive members for electrophotography struggle to simultaneously suppress abnormal discharge due to electric field concentration and ensure sufficient charging performance, leading to image defects like lateral black belt images.

Method used

A conductive member with a conductive layer having a matrix with a volume resistivity greater than 1.0 x 10^12 Ωcm, including a first rubber crosslink and dispersed domains with a second rubber crosslink and electronic conductive agents. The conductive layer has a region T where the volume resistivity of the matrix decreases in depth from the outer surface, while the domain's volume resistivity increases towards the depth direction.

Benefits of technology

The solution effectively suppresses abnormal discharge and horizontal black strip images in defects, while ensuring high discharge performance and preventing image defects due to insufficient charging, thereby contributing to the formation of high-quality electrophotographic images.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669134000016
    Figure 0007669134000016
  • Figure 0007669134000017
    Figure 0007669134000017
  • Figure 0007669134000018
    Figure 0007669134000018
Patent Text Reader

Abstract

To provide a conductive member that can achieve both abnormal discharge due to electric field concentration and electrification failure due to insufficient discharge even in a high-speed process.SOLUTION: There is used a conductive member for electrophotography including a support that has a conductive outer surface and a conductive layer that is provided on the outer surface of the support. The conductive layer has a matrix that includes a first rubber cross-linked material and has a volume resistivity larger than 1.0×1012 Ω cm, and a plurality of domains that are dispersed in the matrix. The domains include a second rubber cross-linked material and an electronic conductive agent. The conductive layer has an area T in which the volume resistivity of the matrix is reduced from the outer surface of the conductive member toward a depth direction.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electroconductive member for electrophotography, a process cartridge, and an electrophotographic image forming apparatus. [Background technology]

[0002] In electrophotographic image forming apparatuses, conductive members are used as charging members and transfer members. The conductive members transport electric charges from the conductive support to their surfaces and impart electric charges to objects in contact with them by discharging or by frictional charging. The charging member, which is one of the conductive members, generates a discharge between itself and the photosensitive drum, thereby charging the surface of the photosensitive drum. If there is a minute defect such as a pinhole on the surface of the photosensitive drum, electric field concentration is likely to occur at the contact point of the charging member, and excessive charge transport, i.e., abnormal discharge, is likely to occur. When abnormal discharge occurs, the charge supplied from the conductive support to discharge and charge the entire longitudinal direction of the conductive member is concentrated on discharging at the minute defect. This causes a phenomenon in which the amount of discharge is reduced in the longitudinal in-phase regions that should be discharged at the same time, and the photosensitive drum is not charged. As a result, the longitudinal in-phase regions that should be discharged at the same time, including the minute defect, have a reduced charging potential, and toner is excessively developed, resulting in a black band-like image defect, so-called a "horizontal black band image."

[0003] Patent Document 1 discloses a means for controlling the volume resistivity of each layer in a conductive member having a multilayer film, thereby suppressing the above-mentioned abnormal discharge. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-108063 A Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 discloses a technique for suppressing the abnormal discharge by setting the volume resistivity of each layer in a conductive member having a multilayer film of an elastic layer and a surface layer (collectively referred to as a conductive layer). In such a configuration, the challenge is to achieve both suppression of abnormal discharge caused by electric field concentration and charging performance. In other words, it was difficult to simultaneously suppress abnormal discharge caused by excessive charge flowing in due to electric field concentration in defects in the photosensitive drum and suppress insufficient discharge caused by increasing resistance to suppress the flow of excessive charge. For example, when the electrical resistance of the entire conductive layer is within a proper range and the volume resistivity of the surface layer is smaller than that of the elastic layer, excessive charge transport cannot be suppressed, and horizontal black bands due to the abnormal discharge may occur. As another example, when the volume resistivity of the surface layer is larger than that of the elastic layer, the function of suppressing excessive charge transport can be realized, but sufficient charge cannot be supplied to the outer surface of the conductive layer in time, particularly during high-speed printing, and image defects due to a decrease in the amount of charge may occur.

[0006] One aspect of the present disclosure is directed to providing a conductive member that has high discharge performance required for a charging member or transfer member for electrophotography, and that suppresses abnormal discharge and horizontal black band images even on a photosensitive drum having defects such as pinholes, while at the same time suppressing a decrease in the amount of charge. Another aspect of the present disclosure is directed to providing a process cartridge that contributes to the formation of high-quality electrophotographic images, and an electrophotographic image forming apparatus capable of forming high-quality electrophotographic images. [Means for solving the problem]

[0007] According to one aspect of the present disclosure, a support having an electrically conductive outer surface; A conductive member for electrophotography having a conductive layer provided on an outer surface of the support, the conductive layer has a matrix containing a first cross-linked rubber and having a volume resistivity of more than 1.0×10 Ω cm, and a plurality of domains dispersed in the matrix; The domain includes a second cross-linked rubber and an electronic conductive agent, and the conductive layer has a region T in which the volume resistivity of the matrix is ​​reduced in a depth direction from the outer surface of the conductive member. death, In the region T, the volume resistivity of the domain increases from the outer surface toward the depth direction. An electroconductive member for electrophotography is provided. Effect of the Invention

[0008] According to one aspect of the present disclosure, a conductive member can be provided that can suppress abnormal discharge and horizontal black band images caused by electric field concentration in defects such as scratches on a photosensitive drum, even when used for a long period of time with a large applied voltage to accommodate higher speeds, while at the same time suppressing the occurrence of image defects such as horizontal charged streak images caused by insufficient charging. According to another aspect of the present disclosure, it is possible to obtain a process cartridge that contributes to the formation of a high-quality electrophotographic image. Furthermore, according to another aspect of the present disclosure, it is possible to obtain an electrophotographic image forming apparatus that can form a high-quality electrophotographic image. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a conceptual diagram of the vicinity of a contact portion between a photosensitive drum and a charging member. [Diagram 2] 2 is a cross-sectional view of a conductive member according to an embodiment of the present disclosure, taken in a direction perpendicular to the longitudinal direction. FIG. [Diagram 3] FIG. 2 is a cross-sectional view of a conductive member according to an embodiment of the present disclosure, taken in a direction perpendicular to the longitudinal direction of a conductive layer. [Figure 4] FIG. 1A is an explanatory diagram of the cut-out direction of a cross section, and FIG. [Diagram 5] FIG. 2 is a conceptual diagram of a process cartridge. [Figure 6] FIG. 1 is a conceptual diagram of an electrophotographic apparatus. [Figure 7]1 is a graph plotting current values ​​from the outermost surface of a conductive layer of a conductive member in a depth direction. [Figure 8] FIG. 2 is a conceptual diagram of an apparatus for observing discharge light generated in a gap between a photosensitive drum and a charging member. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The inventors speculate that the reason why it is difficult to simultaneously prevent the occurrence of abnormal discharge due to concentration of the electric field at the defect and prevent the occurrence of image defects such as horizontal streaks due to insufficient charging in the charging process of a photosensitive drum having a defect such as a pinhole is as follows. The photosensitive drum has a high-resistance photosensitive layer on its surface to maintain the charging potential of the charging member. In an electrophotographic image forming apparatus (hereinafter also referred to as an electrophotographic apparatus), the photosensitive drum abuts against other members such as a developing member, a transfer member, and a cleaning member. Therefore, during the electrophotographic image forming process, the photosensitive drum may develop minute defects such as scratches due to the state of abutment with other members or the influence of foreign matter at the abutment portion with other members. Such defects are becoming more likely to occur as the process speed of electrophotographic apparatuses increases and their lifespans increase.

[0011] The photosensitive layer is formed on a substrate having a conductive surface in order to connect the photosensitive drum to a ground electrode of the main body of the electrophotographic device. The photosensitive layer has a smaller thickness in the defective area than the surrounding non-defective areas, and therefore has a lower electrical resistance. Depending on the size and depth of the defect in the planar direction, the photosensitive layer may hardly function as a resistor in the defective area.

[0012] As a result, the voltage share is significantly reduced at the defective portion of the photosensitive drum. That is, in the conductive path in the area of ​​the charging member where discharge can occur to the defect, the voltage share is increased by the amount of the reduction in the voltage share of the defective portion of the photosensitive drum, and the electric field is increased. Note that in the portion of the photosensitive drum where no defect occurs, all the charge paths in the conductive member have a uniform electric field.

[0013] On the other hand, the behavior of the charging member corresponding to the defect will be explained below. First, an electric charge is supplied to the charging member via a conductive support connected to a power source, and the electric charge is transported through the conductive layer to the surface of the conductive layer in accordance with the electric field formed by the applied voltage, and a discharge occurs in the minute gap between the charging member and the photosensitive drum.

[0014] Here, the charge in the conductive path can be expressed as a=qE / m from the equation of motion F=ma and the electrostatic attractive force F=qE that gives the acceleration, so the acceleration of the charge is proportional to the applied electric field. Therefore, in areas of the photosensitive drum where there is a defect (where the electric field is large), the speed at which the charge is discharged from the surface of the charging member into the gap is faster than in the surrounding non-defective areas.

[0015] Furthermore, conventional charging members have a continuous conductive surface, and the longitudinal region (region where discharge occurs simultaneously) where the micro-gap distance from the photosensitive drum is equal forms an equipotential surface. Therefore, a large amount of charge flows into the discharge occurring at the position corresponding to the defect on the charging member surface due to the effect of a strong electric field being applied from the entire longitudinal region. Generally, the size of a defect such as a scratch on a photosensitive drum is 1 mm in diameter or less, while the longitudinal dimension of a typical charging member exceeds 200 mm, so it is thought that more than 200 times the usual amount of charge flows in.

[0016] Next, the discharge caused by the release of electric charges from the surface is a diffusion phenomenon of an exponentially increasing electron avalanche as the electric charges collide with molecules in the air or with electrodes to generate electrons and positive ions. Therefore, if the release rate of electric charges on the surface of the charged member is high, the electron avalanche is likely to become large.

[0017] In other words, from the above explanation, it is considered that discharge to the defect occurs because the electric field concentration causes the charge release rate from the surface of the charged member to become excessive, and an excessive amount of charge enters from the longitudinal direction, making the amount of discharge charge in the air excessive, and easily resulting in abnormal discharge.

[0018] As a result, in the longitudinal region where the micro-gap distance from the photosensitive drum is equal (region where discharge occurs simultaneously), the non-defective portion has insufficient charge available for discharge. This reduces the charge potential, causing an excessive amount of toner to be developed. As a result, black horizontal stripes may appear in the electrophotographic image at the positions corresponding to the contact points.

[0019] One possible method for suppressing abnormal discharge is to utilize a high-resistance layer, as described in Patent Document 1. For example, if a high-resistance layer is provided as the outermost layer, even if electric field concentration occurs at a defect in the photosensitive drum, the surface layer can block excessive charge movement, suppressing abnormal discharge. However, during high-speed printing, the supply of charge to the outer surface cannot keep up.

[0020] Here, Fig. 1 shows a conceptual diagram of the vicinity of the contact portion 13 between the photosensitive drum 11 and the charging member 12. If the supply of charge cannot keep up, as shown in Fig. 1, the discharge 14 in the gap on the upstream side of the contact portion 13 between the photosensitive drum 11 and the charging member 12 becomes insufficient. As a result, a minute discharge 15 also occurs in the gap on the downstream side of the contact portion 13. Since the discharge on the downstream side of the contact portion 13 with the photosensitive drum 11 occurs with a minute potential difference, it tends to be a very sparse discharge, resulting in a charging horizontal stripe image that appears as sparse stripes on the image. In Fig. 1, an arrow 101 indicates the rotation direction of the charging member 12, and an arrow 103 indicates the rotation direction of the photosensitive drum.

[0021] Another method for suppressing abnormal discharge is to form layers other than the outermost layer of a charging member having a multilayer film from a material with a higher volume resistivity than the outermost layer, thereby suppressing excessive charge transfer. However, in order to suppress a shortage of discharge, it is necessary to introduce a layer with a low resistance surface layer. In this case, in the end, on the surface of the charging member corresponding to the scratched part on the photosensitive drum surface, the charge may wrap around in the equipotential area in the longitudinal direction where discharge should occur at the same time, and black horizontal stripes may occur on the electrophotographic image.

[0022] As described above, it is not easy to achieve both a charging member suppressing abnormal discharge caused by electric field concentration in the case of defects such as scratches on a photosensitive drum and, at the same time, suppressing the occurrence of image defects such as horizontal charging streak images caused by insufficient charging. Therefore, after extensive research, the inventors have discovered that, in order to solve the above problems, a conductive member can be obtained that satisfies the following requirements, thereby suppressing abnormal discharge due to defects and suppressing the occurrence of horizontal charging streak images caused by an insufficient amount of charge. Requirement (1) The conductive layer contains a first cross-linked rubber, and the volume resistivity is 1.0×10 12 The composite material has a matrix having a resistivity of more than Ωcm and a plurality of domains dispersed in the matrix, the domains including a second cross-linked rubber and an electronic conductive agent. Requirement (2) The conductive layer has a region T in which the volume resistivity of the matrix decreases in the depth direction from the outer surface of the conductive member.

[0023] <Requirement (1)> First, we will explain requirement (1). As explained above, abnormal discharge due to defects occurs when the speed of the charge becomes too high in the process of the charge traveling from the conductive support to the conductive layer and then to the conductive member surface. Alternatively, it occurs when an excessive amount of charge flows into a longitudinal region on the surface where the distance of the micro-gap to the photosensitive drum is equal (a region where discharge occurs simultaneously). The inventors consider the process up to the time of reaching the conductive member surface as follows. The acceleration of the charge movement from the support to the outer surface of the conductive layer can be expressed as the following formula (A) from the equation of motion and Ohm's law. In formula (A), F is the electrostatic attractive force (N), m is the mass of the charge (g), and a is the acceleration of the charge (m / s 2 ), q is the charge (C), E is the electric field (V / m), V is the shared voltage of the conductive path (V), and d is the distance of the conductive path over which the shared voltage is applied (m).

[0024]

number

[0025] Equation (A) means that the acceleration a of the charge is proportional to the shared voltage V of the conductive path. That is, the greater the shared voltage V applied to the conductive part, the greater the acceleration of the charge transfer. When the volume resistivity of the conductive layer is constant from the support to the outer surface of the conductive layer, the voltage applied to the conductive portion is also constant from the support to the outer surface of the conductive layer, and therefore the acceleration is also constant. A constant acceleration means that the charge migration speed continues to increase from the support to the outer surface of the conductive layer. Therefore, if there is a defect such as a scratch on the photosensitive drum and an excessive electric field is applied, the acceleration increases and the final arrival speed of the charge is likely to increase. It is very difficult to suppress the acceleration of this charge in a conductive layer having a conductive path that is continuous from the conductive support to the surface of the conductive member, because in the continuous state, the charge continues to accelerate regardless of the volume resistance of the conductive path.

[0026] The inventors considered that in order to prevent the charge from continuing to accelerate, a configuration in which the charge is reliably stopped temporarily after a certain amount of acceleration in the conductive path could be used to effectively suppress the acceleration of the charge. It was also considered that in a conductive layer having a matrix-domain structure with a conductive domain and an insulating matrix structure, after a charge moves within the domain, which is the conductive phase, it always collides with the matrix, which is the insulating phase, and the movement of the charge can be temporarily stopped. As a result, it is considered that the charge remains within the conductive domain and reaches the surface of the conductive member by being transferred between the domains.

[0027] Furthermore, when considered from the viewpoint of the shared voltage, the shared voltage of the insulating matrix with a high volume resistivity is large, while the shared voltage of the conductive domain is small. Therefore, the acceleration of the charge in the domain is significantly suppressed compared to a configuration of interconnected conductive paths to which the shared voltage of the charging bias is applied as it is. Specifically, the matrix of the insulating phase is 1.0×10 12 Having a volume resistivity exceeding Ωcm is essential for exerting the effect of temporarily suspending electric charge, since it can inhibit the passage of electric charge through the matrix. At the same time, in this matrix-domain structure, the conductive domains on the surface of the charging member are independent and there are no connected parts, so it is believed that charge flow is unlikely to occur even on the equipotential surface of the surface. Therefore, it is also possible to suppress the flow of electric charge from an equipotential surface, that is, an equipotential surface, into a defect on the photosensitive drum, in a region in the longitudinal direction where the micro-gap distance from the photosensitive drum is the same (a region where discharge occurs simultaneously).

[0028] As described above, if the charge is simply blocked by a high resistance layer as in Patent Document 1, the charge horizontal streak images occur due to insufficient charge amount. However, the present inventors have found that with the matrix-domain structure, the charge horizontal streak images can also be suppressed at the same time. The matrix-domain structure can achieve a state in which an abundant amount of charge exists in the conductive domains throughout the conductive layer by making the domains conductive with an electronic conductive material, increasing the amount of accumulated charge, and thereby ensuring that the charge remains in the domains and can contribute to discharge. This makes it possible to suppress a decrease in the amount of discharge occurring upstream of the contact portion with the photosensitive drum when used as a charging member, thereby suppressing the phenomenon of sparse discharge occurring downstream of the contact portion, and as a result, it becomes possible to suppress the occurrence of horizontal charging stripe images.

[0029] <Requirement (2)> Next, we will explain requirement (2). As a result of intensive research, the present inventors have come to the realization that, in response to the recent trend of increasing the voltage applied to the charging member in order to increase the amount of discharge per unit time due to the increase in the speed of electrophotographic devices, the requirement (1) alone may not be sufficient to suppress the horizontal black band images. The present inventors further considered that, in order to control the formation of an electron avalanche, which directly governs the amount of discharged charge, it is necessary to control the speed of the charge on the outermost surface when it is discharged from the conductive member. The reason is that within the conductive phase, the charge accelerates in proportion to the voltage shared by the conductive path, and the speed of the charge is the fastest at the outermost surface. This speed is closely correlated with the release of the charge, i.e., discharge, on the surface of the conductive member.

[0030] As explained above, the discharge caused by the release of electric charge from the surface is a diffusion phenomenon of an exponentially increasing avalanche of electric charges as the electric charge collides with molecules in the air and with electrodes to generate electrons and positive ions. In addition, the acceleration and transport of electric charges are also performed in the air according to the electric field, and if the collision frequency with molecules in the air increases and the progress of the avalanche becomes too large, the amount of discharged electric charge increases, resulting in an abnormal discharge. Therefore, in order to suppress the initial speed of the electric charge during the discharge and to minimize the progress of the subsequent avalanche, it is essential to suppress the acceleration of the electric charge on the outermost surface of the conductive member. In order to suppress the acceleration of charges at the outermost surface of the conductive member, measures can be taken to further reduce the shared voltage at the outermost conductive part through which the charges transported from the conductive support while gradually accelerating reach.

[0031] Here, in a method of providing a conductive layer on the outermost surface for the purpose of reducing the voltage shared by the outermost surface, as in Patent Document 1, the flow of charge in the surface direction at the outermost surface occurs, as explained in requirement (1). This causes abnormal discharge, and even if the acceleration can be suppressed, a large amount of charge is involved in the discharge, resulting in abnormal discharge. The inventors have discovered that, in consideration of the suppression of the flow of electric charges at the outermost surface, abnormal discharge can be suppressed at a high level by a configuration having, in addition to requirement (1), a region T in which the volume resistivity of the matrix gradually decreases in the depth direction from the outer surface of the conductive member. By gradually decreasing the volume resistivity of the matrix from the outermost surface of the conductive layer toward the inside of the conductive layer at the outermost surface of the conductive member, the voltage shared by the matrix gradually increases toward the outermost surface of the conductive layer, while the voltage shared by the domain gradually decreases. This makes it possible to reduce the acceleration of charges at the outermost surface while maintaining the ability to supply charges via the domains up to the outermost surface. Furthermore, not only can the acceleration of the charge on the outermost surface be suppressed, but the difference in volume resistivity between the surface and the conductive domain is increased, so the effect of temporarily suspending the charge is also improved. Therefore, the effect of suppressing the charge from wrapping around defects on the photosensitive drum on the outer surface of the conductive layer is also improved. At the same time, the efficiency of charge accumulation in the conductive domain on the outermost surface is also improved, and the effect of suppressing the occurrence of charging lateral stripes due to insufficient discharge charge can be further improved.

[0032] As described above, the conductive layer that satisfies requirements (1) and (2) can suppress the acceleration of charges in the conductive layer and on the outermost surface, even when the applied voltage is increased to increase the speed and the device is used for a long period of time. At the same time, by suppressing the flow of charges on the outermost surface, abnormal discharge to defects in the photosensitive drum can be suppressed. Furthermore, this configuration allows for ample accumulation of charges in the conductive layer, making it difficult for a shortage of discharge charge to occur, and can provide a conductive member that does not produce horizontal charging stripe images.

[0033] The conductive member according to this embodiment will be described with reference to Fig. 2, taking a roller-shaped conductive member (hereinafter, conductive roller) as an example. Fig. 2 is a cross-sectional view perpendicular to the longitudinal direction, which is the axial direction, of the conductive roller. The conductive roller 21 has a cylindrical conductive support 22 and a conductive layer 23 formed on the outer periphery of the support 22, i.e., on the outer surface.

[0034] <Conductive support> The material constituting the conductive support can be appropriately selected from those known in the field of conductive members for electrophotography and those usable as such conductive members. Examples include metals or alloys such as aluminum, stainless steel, conductive synthetic resins, iron, and copper alloys. Furthermore, these may be subjected to oxidation treatment or plating treatment with chromium, nickel, etc. As the type of plating, either electric plating or electroless plating can be used. From the viewpoint of dimensional stability, electroless plating is preferable. As the type of electroless plating used here, nickel plating, copper plating, gold plating, and other various alloy platings can be mentioned. The plating thickness is preferably 0.05 μm or more, and considering the balance between work efficiency and rust prevention ability, the plating thickness is preferably 0.1 μm or more and 30 μm or less. The cylindrical shape of the support may be a solid cylindrical shape or a hollow cylindrical shape (cylindrical shape). The outer diameter of this support is preferably in the range of φ3 mm or more and φ10 mm or less. If a medium resistance layer or an insulating layer exists between the support and the conductive layer, the charge cannot be quickly supplied after the charge is consumed by discharge. Therefore, it is preferable to provide the conductive layer directly on the support, or to provide the conductive layer on the outer periphery of the support only via an intermediate layer made of a thin conductive resin layer such as a primer. As the primer, a known one can be selected and used depending on the rubber material for forming the conductive layer and the material of the support, etc. Examples of the primer material include thermosetting resins and thermoplastic resins, and specifically, materials such as phenolic resins, urethane resins, acrylic resins, polyester resins, polyether resins, and epoxy resins can be used.

[0035] <Conductive layer> As the conductive member satisfying the requirements (1) and (2), for example, a conductive member in which the conductive layer satisfies the following configurations (i) to (iii) is preferable. Structure (i) A matrix-domain structure having domains containing a plurality of electronic conductive materials dispersed in the matrix. Structure (ii) The volume resistivity of the matrix is ​​1.0×10 12 Ω cm or greater than 1.0×10 17 Must be Ω·cm or less. Configuration (iii) The matrix has a region T in which the volume resistivity gradually decreases from the outer surface in the depth direction.

[0036] The above elements (i) to (iii) will be described below. FIG. 3 shows a partial cross-sectional view of the conductive layer in a direction perpendicular to the longitudinal direction of the conductive roller. The conductive layer has a matrix-domain structure having a matrix 3a and a domain 3b. The domain 3b contains conductive particles 3c as an electronic conductive agent. It is assumed that a bias is applied between the conductive support and the member to be charged to a conductive member having a conductive layer in which domains containing an electronic conductive agent are dispersed in the matrix. In the conductive layer at that time, it is considered that the charge moves from the conductive support side of the conductive layer to the opposite side, i.e., the outer surface side of the conductive member, as follows.

[0037] That is, the charge is accelerated and transported according to the voltage distribution in the domain, and then stopped near the interface with the matrix. The charge is then transferred in sequence from the domain located on the conductive support side to the domain located on the opposite side to the conductive support side, and reaches the surface of the conductive layer opposite to the conductive support side (hereinafter also referred to as the "outer surface of the conductive layer"). That is, after being accumulated in a domain, transfer to the next domain is performed in sequence. Furthermore, the domains containing the electronic conductive agent allow for efficient accumulation of charges within the domains, so that it is possible to always arrange a large number of domains with abundant charges within the conductive phase, making it possible to suppress the occurrence of horizontal charging streaks due to insufficient charging, even as the charge gradually stops. Furthermore, the above configurations (i) to (iii) are necessary to reduce the shared voltage within the domain and thereby reduce the acceleration of the charge, and at the same time, to suppress excessive flow of charge from the equipotential surface on the conductive member surface to defects on the photosensitive drum.

[0038] <Configuration (i)> <Matrix-Domain Structure> The matrix-domain structure is essential for stopping the charge in the conductive layer at the interface between the domain and the matrix, and at the same time, suppressing the acceleration of the charge in the domain due to the difference in volume resistivity between the matrix and the domain. Furthermore, this function of stopping the charge at the domain interface suppresses the phenomenon in which a large amount of charge flows toward defects in the photosensitive drum within the equipotential surface on the conductive member surface, and can suppress the amount of discharge charge to the defects. In addition, the high resistance matrix not only suppresses the acceleration of the charge, but also allows an abundant amount of charge to be accumulated within the domain due to the electronic conductive agent contained in the domain, making it possible to suppress the occurrence of horizontal charging streak images caused by insufficient charge.

[0039] <How to confirm matrix-domain (MD) structure> The presence of a matrix-domain structure in the conductive layer can be confirmed by preparing a thin slice from the conductive layer and closely observing the fracture surface formed in the thin slice. Examples of the means for thinning include a sharp razor, a microtome, FIB, etc. In order to observe the matrix-domain structure more accurately, the thin section for observation may be subjected to a pretreatment such as a staining treatment or a deposition treatment, which can favorably obtain a contrast between the domain as a conductive phase and the matrix as an insulating phase. The fracture surface of the formed and, if necessary, pretreated thin section can be observed with a laser microscope, a scanning electron microscope (SEM) or a transmission electron microscope (TEM) to confirm the presence of the matrix domain structure. Observation with a scanning electron microscope (SEM) is preferable as a method for easily and accurately confirming the matrix-domain structure. A thin piece of the conductive layer is obtained by the above-mentioned method, and an image is obtained by observing the surface of the thin piece at 1000 times or more and 10000 times or less. Then, using a commercially available image processing software such as image software (product name: ImageProPlus, manufactured by Media Cybernetics), an 8-bit grayscale image is obtained to obtain a monochrome image with 256 gradations. Next, the black and white of the image are inverted so that the domains in the fracture surface become white, and the image is binarized to obtain an analysis image. The presence or absence of a matrix-domain structure can be determined by the analysis image that has been image-processed to a state in which the domains and matrix are distinguished by binarization. The presence of a matrix-domain structure in the conductive layer can be confirmed when the analysis image includes a structure in which multiple domains exist in an isolated state in a matrix, as shown in Figure 3. The isolated state of the domains may be such that each domain is arranged without being connected to other domains, the matrix is ​​connected in the image, and the domains are divided by the matrix. Specifically, when a 50 μm square in the analysis image is set as the analysis region, the state in which the number of domains existing in an isolated state as described above accounts for 80 percent or more of the total number of domains that do not contact the frame line of the analysis region is considered to have a matrix-domain structure. The above confirmation can be performed by dividing the conductive layer of the conductive member into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction, and then randomly preparing one section from each of the 5 sections, for a total of 20 sections, and carrying out the above measurement to confirm the presence of a matrix-domain structure in the conductive layer.

[0040] <Method of forming matrix-domain structure> For example, the conductive member according to this embodiment can be formed by kneading conductive rubber particles that form domains into a matrix rubber, etc. Among these, a method including the following steps (i) to (iv) is preferred. Step (i): preparing a domain-forming rubber composition (hereinafter also referred to as "CMB") containing carbon black and a second crosslinked rubber; Step (ii): preparing a matrix-forming rubber composition (hereinafter also referred to as "MRC") containing the first rubber cross-linked product; Step (iii): A step of kneading the CMB and the MRC to prepare a rubber composition having a matrix-domain structure. Step (iv): A step of forming a layer of the rubber composition prepared in step (iii) directly or via another layer on a conductive support, and curing (crosslinking) the layer of the rubber composition to form the conductive layer according to the present embodiment.

[0041] Regarding the configuration (i), the volume resistivity of the matrix is ​​determined by the composition of the MRC. The first rubber used in the MRC is preferably a rubber having low electrical conductivity, specifically, for example, at least one selected from the group consisting of natural rubber, butadiene rubber, butyl rubber, acrylonitrile butadiene rubber, urethane rubber, silicone rubber, fluororubber, isoprene rubber, chloroprene rubber, styrene butadiene rubber, ethylene propylene rubber, ethylene propylene diene rubber, and polynorbornene rubber. More preferably, the first rubber is at least one selected from the group consisting of butyl rubber, styrene butadiene rubber, and ethylene propylene diene rubber. In addition, as long as the volume resistivity of the matrix is ​​within the above range, the MRC may contain, as necessary, a filler, a processing aid, a crosslinking agent, a crosslinking aid, a crosslinking accelerator, a crosslinking accelerator aid, a crosslinking retarder, an antiaging agent, a softener, a dispersant, a colorant, etc. On the other hand, in order to keep the volume resistivity of the matrix within the above range, it is preferable that the MRC does not contain an electronic conductive agent such as carbon black.

[0042] Furthermore, with regard to the configuration (i), it is effective to control the following four items (a) to (d). (a) Difference in interfacial tension σ between the CMB and the MRC; (b) The ratio (ηm / ηd) of the viscosity of the CMB (ηd) and the viscosity of the MRC (ηm); (c) Shear rate (γ) and energy content (EDK) during kneading of CMB and MRC in step (iii); (d) Volume fraction of CMB in the mixture of CMB and MRC in step (iii).

[0043] (a) Interfacial tension difference between CMB and MRC Generally, when two incompatible rubbers are mixed, phase separation occurs. This is because the interactions between the same polymers are stronger than the interactions between different polymers, so the same polymers aggregate together, lowering the free energy and stabilizing the mixture. Because the interface of a phase-separated structure comes into contact with different polymers, the free energy is higher than the interior, which is stabilized by interactions between the same molecules. As a result, interfacial tension occurs that tries to reduce the area of ​​contact with different polymers in order to reduce the free energy of the interface. When this interfacial tension is small, the different polymers tend to mix more uniformly in order to increase entropy. A uniformly mixed state is called dissolution, and there is a tendency for the SP value (solubility parameter), which is an indicator of solubility, to correlate with interfacial tension.

[0044] In other words, the difference in interfacial tension between the CMB and the MRC is considered to correlate with the difference in the SP value of the rubber contained in each. The difference in absolute value between the solubility parameter SP value of the first rubber in the MRC and the SP value of the second rubber in the CMB is preferably 0.4 (J / cm 3 ) 0.5 More than 5.0(J / cm 3 ) 0.5 Less than or equal to 0.4 (J / cm 3 ) 0.5 More than 2.2(J / cm 3 ) 0.5 It is preferable to select a rubber that satisfies the following conditions. Within this range, a stable phase separation structure can be formed, and the domain diameter of the CMB can be reduced. Specific examples of the second rubber that can be used in the CMB are as follows, and at least one of these can be used. Specific examples of the second rubber that can be used in the CMB include natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), acrylonitrile butadiene rubber (NBR), styrene butadiene rubber (SBR), butyl rubber (IIR), ethylene propylene rubber (EPM), ethylene propylene diene rubber (EPDM), Chloro At least one selected from the group consisting of prene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (H-NBR), silicone rubber, and urethane rubber (U) is preferred. It is more preferable that the second rubber is at least one selected from the group consisting of styrene-butadiene rubber (SBR), butyl rubber (IIR), and acrylonitrile-butadiene rubber (NBR), and it is even more preferable that the second rubber is at least one selected from the group consisting of styrene-butadiene rubber (SBR) and butyl rubber (IIR).

[0045] The thickness of the conductive layer is not particularly limited as long as the functions and effects of the intended conductive member can be obtained. The thickness of the conductive layer is preferably 1.0 mm or more and 4.5 mm or less. The mass ratio of the domain to the matrix (domain:matrix) is preferably 5:95 to 40:60, more preferably 10:90 to 30:70, and even more preferably 13:87 to 25:75.

[0046] <Method for Measuring SP Value> The SP value can be accurately calculated by creating a calibration curve using a material with a known SP value. This known SP value can also be the catalog value of the material manufacturer. For example, for NBR and SBR, regardless of the molecular weight, the SP value is almost determined by the acrylonitrile and styrene content ratios. Therefore, the rubbers constituting the matrix and the domain are analyzed for the acrylonitrile or styrene content ratio using analytical methods such as pyrolysis gas chromatography (Py-GC) and solid NMR. Thereby, the SP value can be calculated from the calibration curve obtained from a material with a known SP value. Also, for isoprene rubber, the SP value is determined by the isomer structure such as 1,2-polyisoprene, 1,3-polyisoprene, 3,4-polyisoprene, cis-1,4-polyisoprene, and trans-1,4-polyisoprene. Therefore, similar to SBR and NBR, the isomer content ratio can be analyzed by Py-GC and solid NMR, etc., and the SP value can be calculated from a material with a known SP value. The SP value of the material with a known SP value is obtained by the Hansen sphere method.

[0047] (b) Viscosity Ratio of CMB to MRC The closer the viscosity ratio of CMB to MRC (CMB / MRC) (ηd / ηm) is to 1, the smaller the domain diameter can be. Specifically, the viscosity ratio is preferably 1.0 or more and 2.0 or less. The viscosity ratio of CMB to MRC can be adjusted by selecting the Mooney viscosity of the raw rubber used for the CMB and MRC, and by the type and amount of filler. The viscosity ratio can also be adjusted by adding a plasticizer such as paraffin oil to the extent that the formation of the phase separation structure is not hindered. The viscosity ratio can also be adjusted by adjusting the temperature during kneading. The viscosity of the rubber mixture for forming the domain and the rubber mixture for forming the matrix is ​​Mooney viscosity ML based on JIS K6300-1:2013. (1+4) It can be obtained by measuring the rubber temperature during kneading. An example of a device for measuring the Mooney viscosity is a Mooney viscometer (product name: SMV-300RT, manufactured by Shimadzu Corporation).

[0048] (c) Shear rate and energy during mixing of MRC and CMB The faster the shear rate during kneading of MRC and CMB, and the greater the amount of energy during shearing, the smaller the interdomain distance can be. The shear rate can be increased by increasing the inner diameter of the mixing member, such as the blade or screw of the mixer, decreasing the gap between the end face of the mixing member and the inner wall of the mixer, or by increasing the rotation speed. In addition, the energy during shear can be increased by increasing the rotation speed of the mixing member or by increasing the viscosity of the first rubber in the CMB and the second rubber in the MRC.

[0049] (d) Volume fraction p of the domain (volume fraction p of CMB in the mixture of CMB and MRC) The volume fraction p of the CMB in the mixture of CMB and MRC correlates with the probability of the CMB colliding with the MRC. Specifically, when the volume fraction of the CMB in the mixture of CMB and MRC is reduced, the probability of the CMB and MRC colliding with each other decreases. In other words, the interdomain distance can be reduced by reducing the volume fraction of the domains in the conductive layer within a range that provides the required electrical conductivity. The volume fraction p of the domains is preferably 15% or more and 40% or less.

[0050] <Domain diameter> The arithmetic mean value of the equivalent circle diameter of the domains (hereinafter, simply referred to as "domain diameter") is preferably 0.1 μm or more and 5.0 μm or less. By setting the average domain diameter to 0.10 μm or more, the path along which charges move can be more effectively restricted in the conductive layer, more preferably 0.15 μm or more, and even more preferably 0.20 μm or more. Moreover, by making the average value of the domain diameter 5.0 μm or less, the ratio of the surface area to the total volume of the domain, i.e., the specific surface area, can be exponentially increased, and the efficiency of discharging electric charges from the domain can be dramatically improved. For the above reasons, the average value of the domain diameter is preferably made 2.0 μm or less, and more preferably 1.0 μm or less. The method of calculating the domain diameter will be described later.

[0051] <Distance between adjacent domains (hereinafter also referred to as "inter-domain distance")> The arithmetic mean value of the domain distance is preferably 0.2 μm or more and 4.0 μm or less. In order for the conductive layer in which the domains are dispersed in the matrix of the present disclosure to carry sufficient charges to the outer surface of the conductive member and discharge them, the domain distance is preferably 4.0 μm or less, particularly 3.0 μm or less. On the other hand, in order to ensure that the domains are separated by the matrix, which is an insulating region, sufficient charges are accumulated in the domains and at the same time, excessive charges are not applied to the conductive member, the domain distance is preferably 0.2 μm or more, particularly 0.3 μm or more. The method of calculating the domain distance will be described later.

[0052] <Method for measuring domain volume fraction> The volume resistivity of the domain can be measured, for example, by cutting a slice of a given thickness (e.g., 1 μm) containing a matrix domain structure from a conductive layer and contacting a microprobe of a scanning probe microscope (SPM) or an atomic force microscope (AFM) with the domain in the slice. For example, as shown in Fig. 4A, when the longitudinal direction of the conductive member is the X-axis, the thickness direction of the conductive layer is the Z-axis, and the circumferential direction is the Y-axis, the slice is cut out so as to include at least a part of the XZ plane and the flat cross section 42a. Alternatively, as shown in Fig. 4B, the slice is cut out so as to include at least a part of the YZ plane (e.g., 43a, 43b, 43c) perpendicular to the axial direction of the conductive member. For example, a sharp razor, a microtome, a focused ion beam method (FIB), etc. can be used. To measure the volume resistivity, one side of a flake cut from the conductive layer is grounded. Next, the microprobe (cantilever) of a scanning probe microscope (SPM) or atomic force microscope (AFM) is brought into contact with the domain part of the surface of the flake opposite the grounded surface, a DC voltage of 1V is applied for 5 seconds, and the arithmetic mean value is calculated from the ground current value measured for 5 seconds, and the applied voltage is divided by this calculated value to calculate the electrical resistance value. Finally, the resistance value is converted to volume resistivity using the film thickness of the flake. At this time, the SPM or AFM can measure the film thickness of the flake at the same time as the resistance value. The volume resistivity value of the domain in a cylindrical charging member is determined, for example, by cutting out one thin sample from each of the regions obtained by dividing the conductive layer into four in the circumferential direction and five in the longitudinal direction, obtaining the above-mentioned measured values, and then calculating the arithmetic average value of the volume resistivities of a total of 20 samples.

[0053] <Configuration (ii)> · Volume resistivity of the matrix; The volume resistivity of the matrix is ​​1.0×10 12 Ω cm or greater than 1.0×10 17By setting the resistivity at Ω·cm or less, it is possible to prevent the charge from bypassing the domain and moving within the matrix. In other words, after being transported through the conductive domain, the charge can be temporarily stopped at the interface with the matrix. At the same time, since the voltage shared by the matrix is ​​large and the voltage shared by the domain can be reduced, the acceleration of charges within the domain can be suppressed. By setting the volume resistivity of the matrix within the range of the high resistance region as described above, the charge can be reliably retained and transmitted at the interface with each domain, thereby suppressing the acceleration of the charge. Furthermore, by increasing the difference in volume resistivity with the domain, the conductive member surface can suppress the flow of charge into defects in the photosensitive drum. As a result, abnormal discharge and horizontal black bands can be suppressed. Furthermore, since the difference in volume resistivity with the domain is large, sufficient charge can be accumulated in the domain to suppress the shortage of charge amount, and the occurrence of black horizontal stripes due to charging can be suppressed.

[0054] ·Method of measurement of matrix volume resistivity; The volume resistivity of the matrix may be measured in the same manner as in the above <Method for measuring volume resistivity of domain>, except that the measurement location is changed to a location corresponding to the matrix, and the applied voltage during measurement of the current value is changed to 50 V.

[0055] <Configuration (iii)> It is essential to suppress the acceleration of charges in the conductive layer and the flow of charges on the surface of the conductive member, as well as to suppress the rate of charge emission from the surface of the conductive member and suppress the development of an electron avalanche. In order to suppress the rate of charge emission from the surface of the conductive member, it is necessary to have a region T in which the volume resistivity of the matrix gradually decreases in the depth direction from the outer surface. In this region T, the volume resistivity of the domain increases in the depth direction from the outer surface, so that the voltage shared by the matrix gradually increases toward the outermost surface of the conductive layer, while the voltage shared by the domain gradually decreases, which is preferable. In addition to having such a region T, the volume resistivity of the matrix in a first thickness region from the outer surface of the conductive layer to a depth of 5 μm or more to 6 μm or less is R1 (Ωcm), and the volume resistivity of the domain included in the first thickness region is r1 (Ωcm), When the volume resistivity of the matrix in a second thickness region at a depth of t-1 μm or more and t μm or less from the outer surface of the conductive layer is R2 (Ωcm) and the volume resistivity of the domain contained in the second region is r2 (Ωcm), it is preferable that the following formula (1) is satisfied. R1 / r1>R2 / r2 (1)

[0056] <How to check area T> In configuration (iii) (requirement (2)), the surface region T can be confirmed by cutting out a cross-section of the conductive member of the present disclosure, including the outermost surface, and confirming the surface region T using a means capable of two-dimensionally mapping the electrical resistance value in the depth direction of the cross-section. First, a sample is taken out from the conductive member, and the electrical resistance of the thin sample can be measured using a microprobe. Examples of means for thinning include a sharp razor, a microtome, and a focused ion beam method (FIB). Among these, a microtome is preferred because it forms a smooth cross section and can eliminate the surface shape factor as much as possible in the measurement using the microprobe. As a specific means for making measurements with a microprobe, for example, it is preferable to use an SPM or AFM, which can measure the shape and electrical resistance value using a microcantilever. In these methods, the back side of the slice is connected to a ground electrode relative to the measurement cross section, and a voltage is applied to the measurement cross section via a microprobe to scan the cross section, making it possible to visualize the distribution of electrical resistance values. Furthermore, it is possible to measure that the volume resistivity of the matrix decreases in the depth direction from the outermost surface by using a two-dimensional distribution image of the electrical resistance value of the measured cross section. By using a commercially available image processing software such as "Imageproplus" (product name, manufactured by Media Cybernetics), the change in image density accompanying the change in volume resistivity can be quantified, and the point at which the change in volume resistivity from the outermost surface becomes saturated can be set as the boundary of the surface region T. The thickness t of the surface region T is preferably 20 μm or more and 200 μm or less. The thickness t of the surface region T is preferably 20 μm or more in order to suppress the wraparound of the charge on the surface of the conductive member. On the other hand, in order to suppress the excessive suppression of the wraparound of the charge, which leads to insufficient charging, the thickness t of the surface region T is preferably 200 μm or less, and more preferably 100 μm or more in order to suppress excess current due to electric field concentration.

[0057] <How to make area T> The method for producing the surface region T is not particularly limited as long as it is a method that can modify the conductive layer so that the volume resistivity of the conductive layer decreases from the outer surface of the conductive layer, which is the charge discharging surface, in the depth direction. Specific examples of the method include a surface treatment of the conductive layer and a method of adding a surface-transferable material to the material forming the conductive layer. Specifically, electron beam irradiation and heat treatment can be mentioned, which can change the degree of crosslinking of the rubber material used in the conductive member. Among them, surface treatment by electron beam irradiation and heat treatment is preferable. These means work to improve the degree of crosslinking of the rubber material on the surface of the conductive member, which is a rubber roller. Increasing the degree of crosslinking of the rubber material means that the free volume of the polymer of the rubber material is reduced, and the volume shrinks very slightly. This shrinkage can also be confirmed by measuring the outer diameter of the conductive member.

[0058] The surface of the conductive member where the free volume of the polymer of the rubber material is reduced and the surface shrinks has a high electrical resistance due to a decrease in molecular mobility. Therefore, in the conductive member according to the present disclosure, the volume resistivity of the matrix is ​​increased by surface treatment that changes the degree of crosslinking through electron beam irradiation or heat treatment. On the other hand, the domains of the conductive layer according to the present disclosure also simultaneously shrink and the degree of crosslinking increases, but as the rubber shrinks, the distance between the electronic conductive agents in the domains decreases, and the volume resistivity of the domains decreases. In other words, by subjecting a conductive layer having a domain-matrix structure in which the domain contains an electronic conductive agent and the matrix does not contain an electronic conductive agent to electron beam irradiation or heat treatment, the surface region T according to the present disclosure can be formed more effectively. The degree of cross-linking on the surface of the conductive member can be quantified by a method for evaluating molecular mobility, such as the T2 relaxation time that can be measured by pulse NMR. In this manner, when the degree of crosslinking of the rubber material is improved on the surface of a conductive member having a conductive domain containing an electronic conductive agent and a conductive layer with an insulating matrix structure according to the present disclosure, the surface simultaneously experiences high resistance in the matrix and low resistance in the domain. It is possible to control the thickness t of the surface region T by the intensity of the surface treatment as described above. The thickness t of the surface region T can be increased by increasing the intensity of the electron beam irradiation, extending the irradiation time, increasing the heat treatment temperature, or extending the heat treatment time.

[0059] <Volume resistivity of domain> The domain is a conductive phase, and it is necessary to effectively transport the charge within the domain. In order to reduce the shared voltage applied to the domain, the volume resistivity ρd of the domain is set to 1.0×10 1 Ωcm or more 1.0×10 4 Ωcm or less is preferable. 1.0×10 1 If the resistance is Ωcm or more, the increase in the amount of charge supplied is suppressed, and the electrical resistance of the non-conductive matrix can suppress excess current.4 If the resistance is Ωcm or less, the charge transport speed can be prevented from decreasing, so that the charge transfer necessary for discharging and charging is not suppressed, and the charge shortage can be suppressed. As described above, it is preferable to use an electronic conductive agent in order to improve the efficiency of charge accumulation in the domain.

[0060] <Method for measuring volume resistivity of domain> The volume resistivity of the domain may be measured by the same method as that for measuring the volume resistivity of the matrix. The volume resistivity as described above is measured by cutting one thin sample from each of the four regions circumferentially and five regions longitudinally into which the conductive layer is divided, obtaining the above-mentioned measurements, and then calculating the arithmetic average of the volume resistivities of a total of 20 samples.

[0061] <Means for achieving volume resistivity of domain> The volume resistivity of the domain can be adjusted by adjusting the conductivity to a desired value by appropriately using a conductive agent, and by appropriately selecting the type and amount of the conductive agent. The domain comprises a second rubber crosslinked product and an electronic conductive agent. The matrix contains the first cross-linked rubber as a main component, contains almost no electronic conductive agent such as carbon black, and has a higher electrical resistance than the domain. Examples of the electronic conductive agent to be blended in the domain include carbon materials such as carbon black and graphite, conductive oxides such as titanium oxide and tin oxide, metals such as Cu and Ag, and particles that are surface-coated with a conductive oxide or metal to make them conductive, etc. If necessary, two or more of these electronic conductive agents may be blended in appropriate amounts and used. The amount of the electronic conductive agent blended in the domain is preferably 10 parts by mass or more and 200 parts by mass or less, and particularly preferably 20 parts by mass or more and 100 parts by mass or less, per 100 parts by mass of the second rubber. By being in the above range, the volume resistivity of the domain is preferably 1.0×10 to enable a sufficient amount of charge to be supplied even under high-speed processing. 1 Ω cm or more 1.0×10 4 It can be easily controlled to within the range of Ω·cm or less. Among the above-mentioned electronic conductive agents, electronic conductive agents containing conductive carbon black as a main component are preferred because they have high conductivity, high affinity with rubber, and facilitate control of the distance between electronic conductive agents, etc. The type of carbon black to be blended in the domain is not particularly limited.

[0062] In addition, when conductive carbon black is used as the electronic conductive agent, the conductive carbon black to be mixed in the domain is preferably 20 parts by mass or more and 150 parts by mass or less with respect to 100 parts by mass of the second rubber. Particularly preferably, it is 50 parts by mass or more and 100 parts by mass or less. This mixing amount is characterized by being mixed in a relatively large amount as a general conductive member for electrophotography. The conductivity of carbon black is formed by a tunnel current flowing between carbon and carbon. The variation in the amount of this tunnel current correlates with the amount of carbon black added and the volume occupancy rate of the second rubber, and the higher this ratio, the more the variation can be suppressed. Therefore, by being in the above range, discharge unevenness, that is, unevenness in the potential of the photosensitive drum can be effectively suppressed. In addition, the second rubber forming the domain may contain fillers and extenders that are generally used as compounding agents for rubbers in order to adjust the volume resistivity in the same manner as the matrix. As the fillers and extenders, those used in the matrix can be suitably used. The fillers and extenders to be compounded in the domain are preferably 0.1 parts by mass or more and 60 parts by mass or less per 100 parts by mass of the second rubber, depending on the volume resistivity of the selected second rubber.

[0063] As a preferred conductive member satisfying the requirements (1) and (2), a conductive member satisfying the configurations (i) to (iii) has been described above, but it is preferable that the conductive member further satisfies the following configuration (iv), which will be described below. <Configuration (iv)> When the length of the conductive layer in the longitudinal direction is L, cross sections of the conductive layer in the thickness direction are determined at three locations: the center of the conductive layer in the longitudinal direction, and L / 4 from both ends of the conductive layer toward the center. For each of these cross sections, observation areas of 15 μm square are placed at three arbitrary locations in a thickness region from the outer surface of the elastic layer to a depth of 0.1T to 0.9T. At that time, 80% or more of the domains observed in each of the nine observation areas have a cross-sectional area of ​​the electronic conductive agent particles (also called conductive particles) contained in the domain that is 20% or more of the cross-sectional area of ​​the domain. The above configuration (iv) can be defined as the content of the conductive particles in the domain. By filling the domain with the conductive particles in the above amount, the efficiency of charge accumulation in the domain can be improved, and horizontal charging streaks resulting from an insufficient amount of charge can be effectively suppressed.

[0064] <Method for measuring the amount of conductive particles in a domain> First, a slice is prepared in the same manner as in the measurement of the volume resistivity of the matrix described above. However, as described below, the slice is prepared by a cross section perpendicular to the longitudinal direction of the conductive member, and the shape of the domain at the fracture surface of the slice must be evaluated. The reason for this is described below. 4A and 4B show diagrams illustrating the shape of conductive member 41 in three dimensions along three axes, specifically, X, Y, and Z. In Fig. 4A and 4B, the X-axis indicates a direction parallel to the longitudinal direction (axial direction) of the conductive member, and the Y-axis and Z-axis indicate directions perpendicular to the axial direction of the conductive member. FIG. 4A shows an image of a conductive member cut out at a cross section 42a parallel to an XZ plane 42. The XZ plane can rotate 360° around the axis of the conductive member. Considering that the conductive member rotates in contact with the photosensitive drum and discharges when passing through a gap with the photosensitive drum, the cross section 42a parallel to the XZ plane 42 indicates a surface where discharge occurs simultaneously at a certain timing. The surface potential of the photosensitive drum is formed by the passage of a surface equivalent to a certain amount of the cross section 42a. Therefore, in order to evaluate the amount of conductive particle filling in the domain, which correlates with the amount of charge accumulation in the conductive member, the following evaluation is required: That is, rather than analyzing a cross section where discharge occurs simultaneously at a certain moment, such as cross section 42a, an evaluation is required on cross section 43a parallel to YZ plane 43 shown in Fig. 4B, which is perpendicular to the axial direction of the conductive member and allows evaluation of the domain shape including a certain amount of cross section 42a.

[0065] When the longitudinal length of the conductive layer is L, a total of three cross sections are selected: cross section 43b at the longitudinal center of the conductive layer, and two cross sections (43a and 43c) at L / 4 from both ends of the conductive layer toward the center. Regarding the observation positions of the cross sections 43a to 43c, when the thickness of the conductive layer is T, three arbitrary positions are determined in a thickness region from the outer surface of each slice to a depth of 0.1T to 0.9T. When an observation region of 15 μm square is placed at the three determined positions, measurements are performed at a total of nine observation regions. The fracture surface can be formed by, for example, freeze fracturing, cross polishing, or focused ion beam (FIB) methods. In consideration of the smoothness of the fracture surface and pretreatment for observation, the FIB method is preferred. In addition, in order to favorably observe the matrix domain structure, pretreatment such as dyeing or deposition may be performed to favorably obtain contrast between the conductive phase and the insulating phase. The matrix domain structure can be observed on the sections that have been subjected to the formation of the fracture surface and the pretreatment by a scanning electron microscope (SEM) or a transmission electron microscope (TEM). Among these, it is preferable to observe the matrix domain structure by SEM at 1000 to 100,000 magnifications from the viewpoint of the accuracy of quantifying the area of ​​the domain.

[0066] <<Method for measuring the cross-sectional area ratio μr of conductive particles in a domain>> The ratio μr of the cross-sectional area of ​​the conductive particles in the domain can be measured by quantifying the captured image as described above. Nine images are obtained at each observation position using a commercially available image processor such as ImageProPlus (product name, Media Cybernetics) for the fracture surface images obtained by SEM observation. From these images, an analysis area of ​​15 μm square is extracted, and an 8-bit grayscale is performed to obtain a monochrome image with 256 gradations. Next, the black and white of the image is inverted so that the domains in the fracture surface become white, and the image is binarized to obtain a binarized image for analysis.

[0067] The cross-sectional area ratio of the conductive particles in the domain can be measured by quantifying the above-mentioned binary image. The cross-sectional area S of the domain and the sum Sc of the cross-sectional areas of the conductive material in each domain are calculated by using the counting function in the binary image processing software (product name: ImageProPlus, manufactured by Media Cybernetics). Then, the arithmetic average value μr (%) of Sc / S is calculated. In the case of a cylindrical charging member, when the length of the conductive layer in the longitudinal direction is L and the thickness of the conductive layer is T, cross sections in the thickness direction of the conductive layer as shown in Fig. 4B are obtained at three locations, namely, the center of the conductive layer in the longitudinal direction and L / 4 from both ends of the conductive layer toward the center. For each of the obtained cross sections, the above measurements are performed in three arbitrary 15 µm square regions in a thickness region from the outer surface of the conductive layer to a depth of 0.1T to 0.9T toward the support, and the arithmetic average of the measured values ​​from a total of nine regions is calculated.

[0068] <Process cartridge> FIG. 5 is a schematic cross-sectional view of a process cartridge for electrophotography having the conductive member according to the present disclosure as a charging roller. This process cartridge is configured to integrate a developing device and a charging device and be detachable from the main body of an electrophotographic device. The developing device is configured to integrate at least a developing roller 53 and a toner container 56, and may include a toner supply roller 54, a toner 59, a developing blade 58, and an agitating blade 510 as necessary. The charging device is configured to integrate at least a photosensitive drum 51, a cleaning blade 55, and a charging roller 52, and may include a waste toner container 57. The charging roller 52, the developing roller 53, the toner supply roller 54, and the developing blade 58 are each configured to be applied with a voltage.

[0069] <Electrophotographic device> FIG. 6 is a schematic diagram of an electrophotographic device using the conductive member according to the present disclosure as a charging roller. This electrophotographic device is a color electrophotographic device in which the four process cartridges are detachably mounted. Each process cartridge uses toner of each color, black, magenta, yellow, and cyan. The photosensitive drum 61 rotates in the direction of the arrow, is uniformly charged by the charging roller 62 to which a voltage is applied from a charging bias power supply, and an electrostatic latent image is formed on the surface by exposure light 611. Meanwhile, the toner 69 stored in the toner container 56 is supplied to the toner supply roller 64 by the stirring blade 610 and transported onto the developing roller 63. Then, the toner 69 is uniformly coated on the surface of the developing roller 63 by the developing blade 68 arranged in contact with the developing roller 63, and the toner 69 is charged by frictional charging. The electrostatic latent image is developed by the toner 59 transported by the developing roller 63 arranged in contact with the photosensitive drum 61, and is visualized as a toner image.

[0070] The visualized toner image on the photosensitive drum is transferred by a primary transfer roller 612 to which a voltage is applied by a primary transfer bias power supply, onto an intermediate transfer belt 615 supported and driven by a tension roller 613 and an intermediate transfer belt drive roller 614. The toner images of each color are superimposed in order to form a color image on the intermediate transfer belt. A transfer material 619 is fed into the apparatus by a paper feed roller, and is transported between an intermediate transfer belt 615 and a secondary transfer roller 616. A voltage is applied to the secondary transfer roller 616 from a secondary transfer bias power supply, and the secondary transfer roller 616 transfers the color image on the intermediate transfer belt 615 onto the transfer material 619. The transfer material 619 onto which the color image has been transferred is fixed by a fixing device 618, and is then discarded outside the apparatus, completing the printing operation. Meanwhile, the toner remaining on the photosensitive drum without being transferred is scraped off by the cleaning blade 65 and stored in a waste toner storage container 67, and the above-mentioned process is repeated for the cleaned photosensitive drum 61. In addition, the toner remaining on the primary transfer belt without being transferred is also scraped off by the cleaning device 617. EXAMPLES

[0071] <Example 1> (1. Production of Unvulcanized Domain Rubber Composition) [1-1. Preparation of Unvulcanized Domain Rubber Composition] An unvulcanized domain composition was obtained by mixing the materials in the amounts shown in Table 1 in a pressure kneader. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 20 minutes.

[0072] [Table 1]

[0073] [1-2. Preparation of unvulcanized matrix rubber composition] An unvulcanized matrix rubber composition was obtained by mixing the materials in the amounts shown in Table 2 in a pressure kneader. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes.

[0074] [Table 2]

[0075] [1-3. Preparation of rubber composition for forming conductive layer] The rubber composition for forming the conductive layer was prepared by mixing each material in the amounts shown in Table 3 with an open roll. The mixer used an open roll with a roll diameter of 12 inches. The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, followed by 10 thin passes with a roll gap of 0.8 mm.

[0076] [Table 3]

[0077] (2. Preparation of conductive material) [2-1. Preparation of conductive support] A round bar having a total length of 252 mm and an outer diameter of 6 mm and made of free-cutting steel with a surface treated with electroless nickel plating was prepared as a conductive support.

[0078] [2-2. Formation of conductive layer] A die with an inner diameter of 10·0 mm was attached to the tip of a crosshead extruder, which had a conductive support supply mechanism and an unvulcanized rubber roller discharge mechanism, and the temperature of the extruder and crosshead was adjusted to 80°C, and the conductive support conveying speed to 60 mm / sec. Under these conditions, the rubber composition for forming the conductive layer obtained above was supplied from the extruder, and the outer periphery of the conductive support was coated with the rubber composition for forming the conductive layer in the crosshead, obtaining an unvulcanized rubber roller. Next, the unvulcanized rubber roller was placed in a hot air vulcanizing furnace at 160°C and heated for 60 minutes to vulcanize the rubber composition for forming the conductive layer, thereby obtaining a roller with a conductive layer formed on the outer periphery of the conductive base. After that, 10 mm of each end of the conductive layer was cut off, making the longitudinal length of the conductive layer 232 mm. Finally, the surface of the rubber roller obtained above was polished using a rotary grindstone to obtain a conductive roller a1 formed into a crown shape with a diameter of 8.44 mm at each position 90 mm from the center to both ends and a central diameter of 8.5 mm.

[0079] [2-3. Surface treatment of conductive parts] The conductive roller a1 was dried for 60 minutes in a hot air circulating dryer set at a temperature of 200° C. to modify the outer peripheral surface of the roller, thereby preparing an electrophotographic roller A1.

[0080] (3. Characterization) [3-1. Confirmation of matrix-domain structure] The presence or absence of a matrix-domain structure in the conductive layer was confirmed by the following method. A slice was cut out using a razor so that a cross section perpendicular to the longitudinal direction of the conductive layer could be observed. Then, platinum was vapor-deposited on the surface of the slice corresponding to the cross section of the conductive layer. The platinum-deposited surface was photographed at 1,000 times magnification using a scanning electron microscope (SEM) (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) to obtain an SEM image. When a structure in which a plurality of domains are dispersed in a matrix and the matrix is ​​connected was confirmed in the obtained SEM image, it was determined that the matrix-domain structure was "present." As for the electrophotographic roller A1, as shown in FIG. 3, a plurality of domains 3b were dispersed in a matrix 3a, and the matrix had a structure in which the matrix was connected.

[0081] [3-2. Measurement of domain diameter D (equivalent circular diameter of domain) observed from the cross section of the conductive layer] The domain diameter D observed from the cross section of the conductive layer was measured as follows. A thin slice having a thickness of 1 μm was cut from the conductive layer using a microtome (product name: Leica EM FCS, manufactured by Leica Microsystems) at a cutting temperature of −100° C. At this time, the thin slice was cut with a surface perpendicular to the axis of the conductive support. The cutting positions from the conductive layer were set to three positions: the center in the longitudinal direction, and L / 4 from both ends of the conductive layer toward the center, where L is the longitudinal length of the conductive layer. Platinum was vapor-deposited on the surface of the slice corresponding to the cross section of the conductive layer. The platinum-deposited surface was photographed at 5000 times magnification using a scanning electron microscope (SEM) (trade name: S-4800, manufactured by Hitachi High-Technologies Corporation) to obtain an SEM image. Next, the obtained SEM image was converted to 8-bit grayscale using image processing software (trade name: ImageProPlus, manufactured by MediaCybernetics) to obtain a monochrome image with 256 gradations. Next, the black and white of the image were inverted so that the domains in the monochrome image became white, and a binarization threshold was set for the brightness distribution of the image based on the algorithm of Otsu's discriminant analysis method, to obtain a binarized image. For the obtained binarized image, square observation areas with sides of 15 μm were placed at three arbitrary locations in a thickness region of 0.1Th to 0.9Th from the outer surface of the conductive layer (the surface opposite to the surface facing the support) when the thickness of the conductive layer is Th, and the cross-sectional area S of each domain present in each observation area was calculated using the counting function of the image processing software. Next, the domain diameter D was calculated from the cross-sectional area S of each domain. Specifically, D=(4S / π)0.5 was calculated using the area S of the domain. The average value Dave of the calculated domain diameters D was taken as the domain diameter of the electrophotographic roller A1 to be evaluated.

[0082] [3-3. Domain distance] The interdomain distance was calculated as follows. First, the three SEM images obtained in 3-2 above were converted to 8-bit grayscale using an image analyzer (product name: LUZEX-AP, manufactured by Nireco Corporation) to obtain a monochrome image with 256 gradations. Next, the black and white of the image was inverted so that the domains in the fracture surface became white, and a binarization threshold was set for the brightness distribution of the image based on the algorithm of Otsu's discriminant analysis method to obtain a binarized image. From the binarized image, square observation areas with sides of 15 μm were placed at three arbitrary locations in a thickness region of 0.1Th to 0.9Th depth from the outer surface of the conductive layer (the surface opposite to the surface facing the support) when the thickness of the conductive layer is Th, and the arithmetic average value of the wall distance of the domains in each observation area was calculated using image processing software attached to the image forming apparatus. Furthermore, the average value of the arithmetic average values ​​of the nine locations was calculated to be the domain distance of the electrophotographic roller A1 to be evaluated.

[0083] [3-4. Measurement of matrix volume resistivity] To evaluate the volume resistivity of the matrix contained in the conductive layer, the following measurements were carried out using a scanning probe microscope (SPM) (product name: Q-Scope 250, manufactured by Quesant Instrument Corporation) operated in contact mode. First, a slice having a thickness of 1 μm was cut from the conductive layer of the electrophotographic roller A1 using a microtome (product name: Leica EM FCS, manufactured by Leica Microsystems) at a cutting temperature of −100° C. When cutting the slice, the direction of the cross section was set perpendicular to the longitudinal direction of the conductive member, taking into account the direction in which the charge is transported for discharge. Next, in an environment of 23°C and 50% RH, the slice was placed on a metal plate so that one side of the slice corresponding to the cross section of the conductive layer was in contact with the surface of the metal plate.Then, on the side of the slice opposite to the side in contact with the surface of the metal plate, a cantilever of an SPM was brought into contact with a portion corresponding to the matrix, a voltage of 50 V was applied to the cantilever for 5 seconds, the current value was measured, and the arithmetic average value for 5 seconds was calculated. The surface shape of the slice was observed with the SPM, and the thickness of the measurement point was calculated from the height profile obtained. Furthermore, the concave area of ​​the contact part of the cantilever was calculated from the observation results of the surface shape. The volume resistivity was calculated from the thickness and the concave area, and was taken as the volume resistivity of the matrix. The conductive layer was divided into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction, and the above measurements were performed on the slices at 20 points in total, one at a time, from each of the regions. The average value was taken as the volume resistivity R1 of the matrix.

[0084] [3-5. Measurement of domain volume resistivity] The volume resistivity of the domain was measured in the same manner as in 3-4 above, except that the contact point of the cantilever was set to the point corresponding to the domain of the slice, and the voltage applied to the cantilever was set to 1 V. The average value of the values ​​at each measurement point was taken as the volume resistivity of the domain of the electrophotographic roller A1 to be evaluated.

[0085] [3-6. Measurement of thickness t of region T] The conductive layer of the electrophotographic roller A1 was cut out from the outermost surface to a depth of 800 μm at a cutting temperature of −100° C. using a microtome (product name: Leica EM FCS, manufactured by Leica Microsystems) to give a slice having a thickness of 1 μm. Next, in an environment of temperature 23°C and humidity 50% RH, the slice was placed on a metal plate so that one surface corresponding to the cross section of the conductive layer was in contact with the surface of the metal plate. Next, a cantilever of an SPM having a current measurement function was brought into contact with the surface of the slice opposite to the surface of the metal plate, and a current mapping image was obtained by scanning the cantilever while applying a voltage of 50 V to the cantilever. The scanning area was 400 μm square. The obtained current mapping image was converted to 8-bit grayscale using image processing software (product name: ImageProPlus, manufactured by Media Cybernetics) to obtain a monochrome image with 256 gradations. From the obtained monochrome image, data on the line profile of the brightness in the depth direction from the outer surface of the conductive layer toward the support was obtained, and a square wave shown in FIG. 7 was created. The depth position where the slope became 0 when the arithmetic average value of the convex part of the created square wave was plotted against the depth of the conductive layer was taken as t (μm). In FIG. 7, 701 corresponds to the domain, and 703 corresponds to the matrix. 7 corresponds to the outer surface of the electrophotographic roller. The vertical axis represents the current value, and the horizontal axis represents the distance in the depth direction from the outer surface of the electrophotographic roller.

[0086] [3-7. Measurement of volume resistivity of matrix-domain structure in region T] The volume resistivity of the matrix and the domain was determined in the same manner as in [3-4. Measurement of matrix volume resistivity]. The measurement points were selected to be the points corresponding to the matrix and the domain present in a thickness region from 5 μm to 6 μm deep from the outer surface of the electrophotographic roller. The volume resistivity of the obtained matrix was taken as R1 (Ωcm), and the volume resistivity of the domain was taken as r1 (Ωcm). Next, based on the t determined in [3-6], the volume resistivity of the points corresponding to the matrix and the domain was determined in a thickness region from t-1 μm to t μm deep from the outer surface of the conductive layer. The volume resistivity of the obtained matrix was taken as R2 (Ωcm), and the volume resistivity of the domain was taken as r2 (Ωcm). If the following relational expression (1) holds, it is evaluated as "Y", and if it does not hold or if region T does not exist, it is evaluated as "N". R1 / r1>R2 / r2 (1)

[0087] [3-8. Measurement of domain volume fraction] The volume fraction of the domain was calculated by measuring the conductive layer in three dimensions using a FIB-SEM. Specifically, a group of slice images was obtained by repeatedly performing cross-sectioning using a focused ion beam and SEM observation using a FIB-SEM (manufactured by FEI, Inc.) (described in detail above). Next, a three-dimensional image of the conductive layer was constructed from the data of the obtained slice images using 3D visualization and analysis software Avizo (trade name, manufactured by FEI, Inc.). Next, the matrix and the domain were distinguished using the binarization function of the analysis software. Next, the volume of the domain contained in one sample of a cube shape with a side length of 10 μm, which was selected from any one of the three-dimensional images, was calculated. The volume fraction of the domain was measured by cutting a thin slice sample at any one of the arbitrary points in each of the regions obtained by dividing the conductive member into four in the circumferential direction and five in the longitudinal direction, and performing the above measurement. The volume fraction of the domain was calculated from the arithmetic average of the measured values ​​at a total of 20 points.

[0088] (4. Image Evaluation) [4-1. Evaluation of leak resistance - Observation of abnormal discharge from pinholes] To evaluate the leak resistance of the conductive member, the function of suppressing abnormal discharge from a photosensitive drum having a pinhole formed therein was evaluated as follows. First, an electrophotographic device (product name: Laserjet M608dn, manufactured by Hewlett-Packard Company) was prepared, the photosensitive drum was removed from the process cartridge, and a through hole with a diameter of 1 mm reaching the metal tube was drilled to prepare a photosensitive drum for evaluation. Next, the electrophotographic roller A1 and the photosensitive drum for evaluation were left to stand in an environment of a temperature of 15° C. and a humidity of 10% RH for 48 hours in order to acclimate them to the measurement environment. As shown in FIG. 8, a rotatable jig was prepared, which allowed the photosensitive drum 82 for evaluation and the charging member A1 81 to come into contact with each other. Next, as shown in FIG. 8, a high-speed camera 83 (FASTCAM SA5, manufactured by Photron) and an image intensifier 84 (C9547-2, manufactured by Hamamatsu Photonics) were placed in a container 803 that was shielded from external light, and the discharge light generated in the gap between the photosensitive drum 82 and the charging member 81 was observed from the direction of the arrow 801. The observation conditions were: the field of view of the high-speed camera 83 was 1024 pixels × 1024 pixels, the frame rate was 1000 fps, and the gain of the image intensifier 84 was 800. Furthermore, while rotating the photosensitive drum 82 for evaluation at a speed of 200 rpm, a DC voltage was applied to the charging member 81 by a high-voltage power supply 85 (Trek615-3, manufactured by Trek Japan Co., Ltd.) starting from -1000 V and increasing by 100 V. The charging member 81 was placed in contact with the photosensitive drum 82 by pressing both ends with a load of 500 g. The charging member 81 was rotated following the rotation of the photosensitive drum 82. During this process, discharge occurring in the gap between the photosensitive drum 82 for evaluation and the charging member 81 was observed. Then, the voltage at which abnormal discharge occurred, which was observed as a light that was greater than normal discharge at the pinhole portion, was measured as the leakage withstand voltage.

[0089] [4-2. Image evaluation of leak resistance] An electrophotographic device (product name: Laserjet M608dn, manufactured by Hewlett-Packard Company) was prepared. In order to evaluate the electrophotographic device in a high-speed process, the device was modified so that the number of sheets output per unit time was 75 sheets / minute for A4 size paper, which was greater than the number of sheets output in the original. First, the photosensitive drum was removed from the process cartridge of the electrophotographic device, and a through hole (pinhole) with a diameter of 1 mm reaching the metal tube was formed therein to prepare a photosensitive drum for evaluation. The electrophotographic roller A1, the photosensitive drum for evaluation, the electrophotographic apparatus, and the process cartridge were left to stand for 48 hours in an environment of a temperature of 15° C. and a humidity of 10% RH in order to acclimate them to the measurement environment. Next, the electrophotographic roller A1 and the photosensitive drum for evaluation were incorporated into a process cartridge as a charging roller and a photosensitive drum, respectively, and a halftone image was output using this. When leakage occurs at a pinhole, excessive current is generated at the pinhole, and at the same time, discharge is insufficient in the area where discharge should occur (longitudinal direction). As a result, horizontal streaks of high density due to insufficient discharge appear in the image along the axial direction of the pinhole. In this evaluation, the halftone image was observed visually and with a magnifying glass, and the presence or absence of horizontal streaks caused by leakage from the pinhole and the state thereof were evaluated according to the following criteria. Rank A: No horizontal streaks are visible to the naked eye. Also, no dot irregularities are visible when observed with a magnifying glass. Rank B: No horizontal lines are visible to the naked eye. However, dot irregularities can be seen when viewed through a magnifying glass. Rank C: Horizontal streaks are visible to the naked eye, but do not occur every time the photosensitive drum rotates. Rank D: Horizontal streaks are visible to the naked eye and occur with each photosensitive drum cycle.

[0090] [4-3. Evaluation of charging ability by observing discharge light] The charging ability was evaluated by observing discharge light as follows. Specifically, except for reversing the rotation direction of the photosensitive drum, a video was obtained by observing the downstream discharge light generated at the exit of the contact part in the same manner as in [4-1. Evaluation of leak resistance: Observation of abnormal discharge of pinholes]. The recording started 1 second after the start of discharge, and the recording time was 2 seconds. For the observed video, Imageproplus was used to calculate the percentage of frames in which downstream discharge could be observed out of a total of 2000 frames in the observed video. The higher this percentage, the more insufficient the electrical resistance is, indicating a lower level of charging horizontal streaks.

[0091] [4-4. Evaluation of charging ability] The laser printer used in the above "Evaluation of leak resistance" was used to form the evaluation image. As in the above "Evaluation of charging ability", the electrophotographic roller A1, the laser printer, and the process cartridge were left in a low temperature and low humidity environment (LL environment) of 15°C / 10% RH (relative humidity) for 48 hours in order to acclimate them to the measurement environment, and the evaluation image was formed in the same environment. An unprocessed electrophotographic photoreceptor (photoreceptor drum) was used. Using this, Vd developed images and halftone images were output and evaluated. Here, the Vd developed image is an image in which toner is developed without drawing dots by exposure under image output conditions that form a solid white image. Specifically, it is a means of controlling the developing bias using an external power source (trek615-3, manufactured by Trek Japan) to develop toner on paper without exposure. This means is an image that allows for more detailed evaluation of charging unevenness compared to halftone images formed by controlling dots. The occurrence of horizontal streak-like defects due to a decrease in the charging ability of the charging roller was evaluated according to the following criteria. The evaluation results are shown in Table 8. Rank A: No horizontal streak-like image defects were observed in either the Vd developed image or the halftone image. Rank B: Horizontal streak-like image defects are observed in part of the Vd developed image, but horizontal streak-like image defects are not observed in the halftone image. Rank C: A horizontal streak-like image defect is observed over the entire surface of the Vd-developed image, and a horizontal streak-like image defect is observed in a part of the halftone image. Rank D: Horizontal streak-like image defects are observed over the entire surface of a halftone image.

[0092] <Examples 2 to 20> The unvulcanized domain rubber composition and the unvulcanized matrix rubber composition according to each Example were prepared in the same manner as the unvulcanized domain rubber composition and the unvulcanized matrix rubber composition according to Example 1, except that the rubber type, the type of conductive particles, and the amount of addition were changed as shown in Table 4-1. Table 4-1 also shows the SP value difference and the viscosity ratio ((ηd / ηm)) between the first rubber and the second rubber. Further, the rubber compositions for forming conductive layers according to each Example were prepared in the same manner as the rubber composition for forming conductive layers according to Example 1, except that the obtained unvulcanized domain rubber composition and unvulcanized matrix rubber composition were mixed in the ratios shown in Table 4, and the types and amounts of vulcanizing agents and vulcanization accelerators were as shown in Table 4-1. In Table 4, the amounts (phr) of the vulcanizing agents and vulcanization accelerators are the amounts per 100 parts by mass of the mixture of the unvulcanized matrix rubber composition and the unvulcanized domain rubber composition. Except for using the obtained rubber composition for forming a conductive layer and setting the temperature and time of the surface treatment as shown in Table 4-2, the conductive layer was formed in the same manner as in Example 1 to prepare electrophotographic rollers A2 to A20. Details of the materials related to the abbreviations in Table 4-1 are shown in Table 5. The evaluation results of the conductive members according to Examples 1 to 20 are shown in Tables 6-1 and 6-2.

[0093] [Table 4-1]

[0094] [Table 4-2]

[0095] [Table 5]

[0096] [Table 6-1]

[0097] [Table 6-2]

[0098] <Comparative Example 1> [Preparation of Rubber Composition for Forming Conductive Layer] The materials shown in Table 7 below were mixed in an open roll to prepare a rubber composition for forming a conductive layer according to this comparative example. A conductive roller Ca1 was produced in the same manner as the conductive roller a1 in Example 1, except that this rubber composition for forming a conductive layer was used.

[0099] [Table 7]

[0100] [Preparation of surface layer coating solution CS1] A resin mixture was prepared by mixing melamine resin (product name: Amidea G821-60, manufactured by DIC Corporation) and polyester (product name: Vylon 30SS, manufactured by Toyobo Co., Ltd.) in a mass ratio of 35:65. To 100 parts by mass of the resin mixture, 8 parts by mass of a fluororesin (product name: Lubron L-2, manufactured by Daikin Industries, Ltd.) as a filler and 25 parts by mass of carbon black (product name: FW200, manufactured by Cabot Corporation) as a conductive agent were added to prepare coating solution CS1 for the surface layer of this comparative example.

[0101] [Preparation of electrophotographic roller CA1] The conductive roller Ca1 was dipped into the surface layer coating liquid CS1 and heated at a temperature of 160° C. for 30 minutes to prepare an electrophotographic roller CA1. The obtained electrophotographic roller CA1 was evaluated in the same manner as in Example 1. In addition, for the electrophotographic roller CA1, since the conductive layer did not have a clear matrix-domain structure, evaluations [3-2], [3-3], [3-5], and [3-8] were not performed. Also, since the conductive layer did not have a surface region T, the volume resistivity measurements for evaluations [3-6] and [3-7] were not performed. The electrophotographic roller CA1 according to this comparative example differs from the electrophotographic roller according to the present disclosure in that the outer surface of the electrophotographic roller is not constituted by a conductive layer. The image evaluation rank in the evaluation [4-2] of the electrophotographic roller CA1 according to this comparative example was rank C. This is believed to be because the wraparound of charge on the outer surface of the electrophotographic roller CA1 could not be suppressed. Moreover, the image evaluation rank in the evaluation [4-4] was rank D. This is believed to be because the amount of discharge from the outer surface of the electrophotographic roller CA1 was insufficient.

[0102] <Comparative Examples 2 to 5> [Preparation of Rubber Compositions Ca2 to Ca5 for Forming Conductive Layer] An unvulcanized domain rubber composition (CMB) and an unvulcanized matrix rubber composition (MRC) having the compositions shown in Table 8-1 were prepared in the same manner as in [1-1] and [1-2] of Example 1. The obtained CMB, MRC and materials shown in Table 8-1 were used in the compounding ratios shown in Table 8-2 in the same manner as in [1-3] of Example 1 to prepare rubber compositions Ca2 to Ca5 for forming a conductive layer.

[0103] [Table 8-1]

[0104] [Table 8-2] In Table 8-2, the compounding ratio (phr) of the vulcanizing agent and vulcanization accelerator is the compounding ratio relative to 100 parts by mass of the rubber mixed with CMB and MRC.

[0105] [Preparation of conductive rollers Ca2 to Ca5] Conductive rollers Ca2 to Ca5 were produced in the same manner as in Comparative Example 1, except that the conductive layer-forming rubber compositions Ca2 to Ca5 were used.

[0106] [Preparation of surface layer coating solution CS2] A binder resin coating solution for forming a surface layer was prepared by the following method. Under a nitrogen atmosphere, 100 parts by mass of acrylic polyol (DC2016, Daicel Chemical Industries) was gradually added dropwise to 27 parts by mass of polymeric MDI (product name: Millionate MR200, Nippon Polyurethane Industry Co., Ltd.) in a reaction vessel while maintaining the temperature in the reaction vessel at 65°C. After the addition was completed, the mixture was reacted at 65°C for 2 hours. The resulting reaction mixture was cooled to room temperature to obtain an isocyanate-terminated prepolymer PC-1 with an isocyanate group content of 4.3%. 41 parts by mass of isocyanate-terminated prepolymer PC1, 59 parts by mass of isocyanate A / isocyanate B=4 / 3 (Vestanat B1370 manufactured by Degussa / Duranate TPA-880E manufactured by Asahi Kasei Chemicals), and 20 parts by mass of a quaternary ammonium salt (trade name: Adeka Cizer LV70 manufactured by ADEKA) as an ion conductive agent were dissolved in methyl ethyl ketone (MEK) to adjust the solid content to 27% by mass. 270 g of the mixed solution and 200 g of glass beads with an average particle size of 0.8 mm were placed in a 450 mL glass bottle and dispersed for 12 hours using a paint shaker disperser to obtain a surface layer coating solution CS2.

[0107] [Preparation of coating solution CS3 for forming surface layer] Surface layer coating liquid CS3 was prepared in the same manner as Surface layer coating liquid CS2, except that the blending amount of the ion conductive agent in Surface layer coating liquid CS2 was set to 1 part by mass.

[0108] [Production of electrophotographic roller CA2] The conductive roller Ca2 was heated at a temperature of 200° C. for 60 minutes for surface treatment to produce an electrophotographic roller CA2 according to Comparative Example 2. The obtained electrophotographic roller CA2 was evaluated in the same manner as in Example 1. The electrophotographic roller CA2 was subjected to a surface treatment, and the volume resistivity of the conductive layer was reduced from the outer surface to the depth direction, forming a region T. However, the volume resistivity of the matrix was 1.0×10 12 significantly smaller than Ω·cm. The electrophotographic roller CA2 was ranked D in the image evaluation in the evaluation [4-2]. This is because the volume resistivity of the matrix is ​​1.0×10 12 This is thought to be because, since the electrical resistance was below Ω·cm, the charge was transferred from the equipotential surface on the surface of the longitudinal region (region where discharge occurs simultaneously) where the distance of the micro-gap to the photosensitive drum is the same. The image evaluation rank for evaluation [4-4] was rank D. This is because the volume resistivity of the matrix is ​​1.0×10 12 This is thought to be because the electrical resistance was below Ω·cm and the charge moved through the matrix, making it impossible to suppress the acceleration of the charge.

[0109] [Production of electrophotographic roller CA3] The conductive roller Ca3 was dipped (dipped) into the surface layer coating solution CS2 by holding the upper end of the roller with its longitudinal direction in the vertical direction, and then pulled up. The dipping time was 9 seconds, and the roller pulling speed was adjusted so that the initial speed was 30 mm / sec and the final speed was 3 mm / sec, and the speed was changed linearly with respect to time between 30 mm / sec and 3 mm / sec. After dip coating, the roller was air-dried at 23° C. for 30 minutes. The roller was then dried in a hot air circulating dryer at 80° C. for 1 hour, and then dried at 160° C. for 1 hour to form a surface layer, thereby producing an electrophotographic roller CA3 according to Comparative Example 3. The obtained electrophotographic roller CA3 was evaluated in the same manner as in Example 1. The electrophotographic roller CA3 according to this comparative example differs from the electrophotographic roller according to the present disclosure in that the electrophotographic roller does not have a conductive layer forming the outer surface thereof, but instead has a highly conductive resin layer as a surface layer. The image evaluation rank for the evaluation [4-2] of the electrophotographic roller CA3 was rank D. This is thought to be because the outer surface of the electrophotographic roller CA3 was composed of a surface layer with a low volume resistivity, and therefore the intrusion of electric charges could not be suppressed.

[0110] [Preparation of CA4 roller for electrophotography] An electrophotographic roller CA4 according to Comparative Example 4 was produced in the same manner as the electrophotographic roller CA3, except that surface layer coating liquid CS3 was used. The obtained electrophotographic roller CA4 was evaluated in the same manner as in Example 1. The electrophotographic roller CA34 according to this comparative example differs from the electrophotographic roller according to the present disclosure in that a conductive layer does not constitute the outer surface of the electrophotographic roller, and a resin layer with low conductivity is provided as a surface layer. The image evaluation rank for the evaluation [4-4] of the electrophotographic roller CA4 was rank D. This is thought to be because the outer surface of the electrophotographic roller CA4 is composed of a surface layer with low electrical conductivity, and the amount of discharge from the outer surface was insufficient.

[0111] [Preparation of electrophotographic roller CA5] The conductive roller Ca3 was used as it was as the electrophotographic roller CA5 according to Comparative Example 5, and was subjected to the same evaluation as in Example 1. Since the electrophotographic roller CA5 was not subjected to the surface treatment of the conductive layer, and therefore the conductive layer did not have the region T, the volume resistivity measurements according to the evaluations [3-6] and [3-7] were not performed. The image evaluation rank for the evaluation [4-2] of the electrophotographic roller CA5 was rank D. This is considered to be because the conductive layer of the electrophotographic roller CA5 does not have the region T, and the acceleration of the charge moving between the domains could not be suppressed.

[0112] [Production of electrophotographic roller CA6] Except for using the conductive roller Ca4, the electrophotographic roller CA6 according to Comparative Example 6 was produced in the same manner as the electrophotographic roller CA2. The obtained electrophotographic roller CA6 was evaluated in the same manner as in Example 1. Although the surface treatment was performed, since the matrix contains a conductive agent, an increase in the volume resistivity from the outer surface of the conductive layer in the depth direction was observed. This is considered to be due to the fact that the distance between the conductive agents on the surface became closer due to the increase in the crosslinking degree and shrinkage of the matrix during the surface treatment. The electrophotographic roller CA6 was ranked D in the image evaluation in the evaluation [4-2]. This is considered to be because the acceleration of the charge moving between the domains could not be suppressed. The image evaluation in the evaluation [4-4] was also ranked D. This is because the volume resistivity of the matrix was 1.0×10 12 This is thought to be because the resistivity was below Ω·cm, and therefore sufficient charge could not be accumulated in the domain.

[0113] [Production of electrophotographic roller CA7] Except for using the electrophotographic roller Ca5, an electrophotographic roller CA7 according to Comparative Example 7 was produced in the same manner as the electrophotographic roller CA2. The image evaluation rank for the evaluation [4-2] of the electrophotographic roller CA7 was rank D. This is thought to be because, like the electrophotographic roller CA6, the matrix of the electrophotographic roller CA7 contains a conductive agent, and charges move through the matrix, so that the acceleration of charges could not be suppressed. Also, the image evaluation rank for the evaluation [4-4] of the electrophotographic roller CA7 was rank D. This is thought to be because the domain in the conductive layer of the electrophotographic roller CA7 does not contain an electroconductive agent, so the amount of discharge from the outer surface of the electrophotographic roller CA7 was insufficient. Table 9 shows the configurations and surface treatment conditions of the electrophotographic rollers according to Comparative Examples 1 to 7. Moreover, the evaluation results of Comparative Examples 1 to 7 are shown in Tables 10-1 and 10-2.

[0114] [Table 9]

[0115] [Table 10-1]

[0116] [Table 10-2] [Explanation of symbols]

[0117] 21 Conductive materials 22 Support 23 Conductive layer 3a Matrix 3b Domain 3c Electronic Conductive Agent 41 Conductive materials

Claims

1. a support having an electrically conductive outer surface; A conductive member for electrophotography having a conductive layer provided on an outer surface of the support, The conductive layer contains a first cross-linked rubber and has a volume resistivity of 1.0×10 12 a matrix having a diameter greater than Ω cm and a plurality of domains dispersed in the matrix; the domain comprises a second rubber crosslinked product and an electronic conductive agent; the conductive layer has a region T in which the volume resistivity of the matrix is ​​reduced in a depth direction from an outer surface of the conductive member, A conductive member for electrophotography, wherein in the region T, the volume resistivity of the domain increases from the outer surface toward the depth direction.

2. The conductive member according to claim 1 , wherein the thickness t of the region T is 20 μm or more and 200 μm or less.

3. a volume resistivity of the matrix in a first thickness region from an outer surface of the conductive layer to a depth of 5 μm or more to 6 μm or less is R1 (Ωcm), and a volume resistivity of the domain included in the first thickness region is r1 (Ωcm), When the volume resistivity of the matrix in a second thickness region from the outer surface of the conductive layer to a depth of t-1 μm or more to t μm or less is R2 (Ωcm), and the volume resistivity of the domain included in the second thickness region is r2 (Ωcm), The conductive member for electrophotography according to claim 1 or 2, which satisfies the following formula (1): R1 / r1>R2 / r2 (1).

4. The volume resistivity ρd of the domain present in the conductive layer is 1.0×10 1 Ωcm or more 1.0×10 4 The conductive member according to any one of claims 1 to 3, having a resistivity of Ωcm or less.

5. 5. The conductive member according to claim 1, wherein a volume fraction p of the domains present in the conductive layer is 15% or more and 40% or less.

6. The difference in absolute value between the SP value of the first rubber constituting the first cross-linked rubber product and the SP value of the second rubber constituting the second cross-linked rubber product is 0.4 (J / cm 3 ) 0.5 More than 5.0 (J / cm 3 ) 0.5 The conductive member according to any one of claims 1 to 5, wherein:

7. 7. The conductive member according to claim 6, wherein the first rubber is a cross-linked product of at least one rubber selected from the group consisting of natural rubber, butadiene rubber, butyl rubber, acrylonitrile butadiene rubber, urethane rubber, silicone rubber, fluororubber, isoprene rubber, chloroprene rubber, styrene butadiene rubber, ethylene propylene rubber, ethylene propylene diene rubber, and polynorbornene rubber.

8. The conductive member according to claim 6 or 7, wherein the second rubber is a cross-linked product of at least one rubber selected from the group consisting of natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), acrylonitrile butadiene rubber (NBR), styrene butadiene rubber (SBR), butyl rubber (IIR), ethylene propylene rubber (EPM), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (H-NBR), silicone rubber, and urethane rubber (U).

9. The conductive member according to any one of claims 6 to 8, wherein the first rubber is a styrene-butadiene rubber, and the second rubber is an acrylonitrile-butadiene rubber.

10. The conductive member according to any one of claims 6 to 8, wherein the first rubber is a butadiene rubber, and the second rubber is a styrene-butadiene rubber.

11. 9. The conductive member according to claim 6, wherein the first rubber is isoprene rubber, and the second rubber is acrylonitrile butadiene rubber or styrene butadiene rubber.

12. The conductive member according to any one of claims 1 to 8, wherein the electronic conductive agent is carbon black.

13. The conductive member according to any one of claims 1 to 12, which is a charging member.

14. 14. A process cartridge for electrophotography, which is configured to be detachably mountable to a main body of an electrophotographic image forming apparatus, and which comprises the conductive member according to claim 1.

15. 14. An electrophotographic image forming apparatus comprising the conductive member according to claim 1.

Citation Information

Patent Citations

  • Semiconductive roll

    JP1998254215A

  • Conductive member, processing cartridge and electrophotographic device

    JP2001092221A

  • Conductive member and its manufacturing method

    JP2001109232A

  • Electrifying member

    JP2002108063A

  • Conductive rubber elastic material, charging member and electrophotographic device

    JP2012163954A